Analysis of the Production Performance of Holstein-Friesian Cattle in Sudan (Journal of Veterinary Medicine and Animal Production, 2022)
This research was conducted to investigate the effect of genetic and non-genetic factors on productive traits in Holstein-Friesian cattle at Dairy Land Farm in Khartoum state (Sudan). The data set used covered the period of eighteen years (1984-2002). It comprised 47 sires and 720 cows with 2400 records extending from first to fifth lactation. The data were statistically analyzed using Harvey’s least- squares computer program (1990). The least squares mean of lactation milk yield (LMY), daily milk yield (DMY), lifetime production (LTP), dry period (DP) and lactation length(LL) were 3055 kg, 11 kg, 8069 kg, 130 days and 290 days, respectively. The sires had a highly significant (P< 0.001) effect on LMY, LTP (P< 0.01) and LL (P< 0.05). Year of birth had a significant (P< 0.05) influence on LTP. The calving year-season and parity had a highly significant (P< 0.001) effect on LMY, DMY, LL and DP (P< 0.01, P< 0.05, respectively). The linear regression on lactation length had a highly significant (P< 0.001) effect on LMY and DP. In addition, the linear regression on dry period and milk yield had a highly significant (P< 0.001) effect on LL. The heritability of studied productive traits were low, this is probably a result of the artificial selection of the herds under study. The genetic correlations were 0.27± 0.35 between DP and LTP, 0.87± 0.16 between LMY and LL and -0.20± 0.42between LMY and DP while phenotypic correlations between the same traits were 0.28, 0.61and 0.02, respectively and the environmental correlations were 0.28, 0.58and 0.05, respectively). The study concluded that the performance of pure Holstein-Friesians was well below their performance in temperate regions, which probably reflects differences in the environment and levels of management. Taking into account the higher cost of management crossbreeding rather than pure breeding may be a more viable option.
Keywords: Holstein-Friesian; milk yield; production; heritability; correlation